ASSESSMENT OF CORRELATION IN GENDER AND AGE WITH LIPOPROTEIN LEVELS IN HYPERLIPIDEMIA PATIENTS - A, Anil Babu; S, Rani; Kg, Revikumar; Mattumal, Shafeeque; Ug, Unnikrishnan (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The main objective of the study was to monitor and compare the correlation between the age and gender with the serum lipoprotein levels in the hyperlipidemia patients. Methods: The entire study was performed only after getting approval from the Institutional Ethics Committee. This is a prospective observational study and conducted in Department of Cardiology of a tertiary care teaching hospital. A total of 520 patients were included and the data collected by data entry form, and the results were thoroughly analyzed using various statistical tools for its relevance and significance. Results: From the total study population (n=520), the majority was males 271 (52.1%) than the female population 249 (47.9%). The minimum age in the study population identified was 40 (years) and the maximum age was 89 (years). The average age of the study population was found to be 60.94±13.062 (years). The mean averages of total cholesterol in males 217.48±39.33 mg/dL compared to females 231.05±55.05 mg/dL, triglycerides in males were 209.01±73.08 mg/dL compared to females 235.71±97.16 mg/dL, low-density lipoproteins in males were 156.42±37.02 mg/dL compared to females 164.19±43.17 mg/dL, and in case of high-density lipoproteins it was 32.61±6.34 mg/dL compared to females 31.48±6.53 mg/dL. Conclusion: From the entire study, it was concluded that the prevalence rate is a more common in male population. The incidence rate is too high in younger age population. The correlation of age and gender is directly proportional to the incidence of hyperlipidemia. Keywords: Hyperlipidemia, Cardiology, Gender, Age.